Speed and accuracy of text-messaging emergency department electrocardiograms from a small community hospital to a provincial referral center. (March 2016) - Scheuermeyer, Frank Xavier; Grunau, Brian E; Findlay, Timothy; Grafstein, Eric; Christenson, Jim; Lang, Eddy; Rowe, Brian; Ho, Kendall
Background: Currently, transmission of electrocardiograms (EKGs) from a small emergency department (ED) to specialists at referral hospitals can be a time-consuming and laborious process. We investigate whether text messaging by use of short message service (SMS) of EKGs from a small hospital to consultants at a large hospital is rapid and accurate. Methods: This study involved a one-month prospective evaluation of consecutive EKGs recorded in a small community ED. Investigators obtained de-identified photographs of each EKG via a mobile phone camera. Each EKG picture, along with a brief patient clinical history, was sent via SMS to on-call emergency physicians located at a large referral care site. All images were evaluated solely on a mobile phone. The primary outcome was the proportion of SMS that were received within two minutes of being sent. As a secondary outcome, the intra-rater evaluation of the initial EKG and the SMS EKG image were compared on 13 standardized features. The tertiary outcome was cost of text messaging. Results: A total of 298 patients (14.6%) had 409 EKGs performed and a total of 926 SMS were sent. 921 SMS (99.5%, 95% confidence interval (CI) 98.7–99.8%) arrived within two minutes with a median transmission time of nine seconds (interquartile range (IQR) 3–32 s). Between the gold standard original EKG, and the interpretation of the texted image, six out of 409 (1.5%, 95% CI 0.6–3.3%) had any differences recorded, across all 13 categories. Overall, the study cost 4.1 cents per texted image. Conclusions: Systematic text messaging of ED EKGs from a small community hospital to a referral center is a rapid, accurate, portable, and inexpensive method of data transfer. This may be a safe and effective strategy to communicate vital patient information.